Prevalence, genetic variants and clinical implications of G-6-PD deficiency in Burkina Faso: a systematic review. Issue 1 (December 2017) - Ouattara, Abdoul; Yameogo, Pouiré; Traore, Lassina; Diarra, Birama; Assih, Maléki; Compaore, Tegwindé; Obiri-yeboah, Dorcas; Soubeiga, Serge; Djigma, Florencia; Simpore, Jacques
Abstract Background It is now well-known that some antimalarials such as primaquine may induce severe hemolytic anemia in people with G-6-PD deficiency. Antimalarial drug prescriptions must, therefore take into account the patient's G-6-PD status in malaria endemic areas such as Burkina Faso, where the prevalence of this genetic abnormality is relatively high. Although great clinical heterogeneity is observed depending on the molecular nature of the deficiency and the residual enzyme activity in the red blood cell, there is very poor data on the prevalence of G-6-PD deficiency and the distribution of involved genetic variants in Burkina Faso. In this systematic review, we present a synthesis of the various studies carried out on the G-6-PD deficiency in Burkina Faso in order to determine its prevalence, probable distribution of the genetic variants involved and their clinical implications for a national systematic screening policy among the groups most vulnerable to malaria. Methods A systematic review was carried out to analyze available published data on the prevalence, phenotypes and mutations responsible for G-6-PD deficiency in Burkina Faso. The key words used were "G-6-PD deficiency AND Burkina Faso" or "Déficit en G-6-PD AND Burkina Faso" in French. To identify the relevant articles, two independent reviewers reviewed the titles, abstracts and the full text of the selected papers. Results An average prevalence of 16.6% (183/1100; CI 95%: 0.145–0.190) and 6.5% (69/1066; CI 95%: 0.051–0.081) of G-6-PD deficiency was found respectively in men and women in this systematic review. Although the predominance (99.8% of G-6-PD deficient cases) of 202A/376G G-6-PD A- variant, the Santamaria and Betica Selma variants were identified in Burkina Faso. Independently of the method used, the enzymatic deficiency was significantly higher in males (2.5–20.5%) compared to females (3.3–12.3%). Conclusion This systematic review suggests that despite the ubiquity of the 202A/376G G-6-PD A- variant in Burkina Faso, it will be necessary to consider the Santamaria and Betica Selma variants although their frequencies remain to be specified. A systematic screening of the G-6-PD deficiency is also needed to prevent the occurrence of iatrogenic hemolytic accidents. Résumé Contexte Il est. actuellement bien connu que certains antipaludiques comme la primaquine, peuvent induire des crises d'anémie hémolytique graves chez les personnes présentant un déficit en G-6-PD. Les prescriptions de médicaments antipaludiques doivent donc tenir compte du statut G-6-PD du patient dans les zones d'endémie du paludisme comme le Burkina Faso où la prévalence de cette anomalie génétique est. relativement élevée. En dépit d'une grande hétérogénéité clinique observée selon la nature moléculaire du déficit et l'activité résiduelle de l'enzyme dans le globule rouge, il existe très peu de données sur la prévalence du déficit en G-6-PD et la distribution des variants génétiques en cause au Burkina Faso. Dans cette revue de la littérature nous présenterons la synthèse des différents travaux réalisés sur le déficit en G-6-PD au Burkina Faso afin de déterminer sa prévalence, la distribution probable des variants génétiques en cause et leurs implications cliniques en vue d'une politique nationale de dépistage systématique au sein des groupes les plus vulnérables au paludisme. Méthodes Une revue systématique a été réalisée pour analyser les données publiées disponibles sur la prévalence, les phénotypes et les mutations du déficit en G-6-PD au Burkina Faso Les mots clés utilisés étaient « G6PD deficiency AND Burkina Faso » en anglais ou « Déficit en G6PD AND Burkina Faso en français ». Pour identifier les articles pertinents, deux examinateurs indépendants ont examiné les titres, les résumés et le texte intégral des articles retenus. Résultats Une prévalence moyenne de 16, 6% (183/1100; IC 95%: 0, 145–0, 190) et 6, 5% (69/1066; IC 95%: 0, 051–0, 081) du déficit en G-6-PD a été observée respectivement chez les hommes et les femmes dans cette revue systématique. Malgré la prédominance (99, 8% des cas de déficients en G-6-PD) du variant G-6-PD A- 202A/376G, les variants Santamaria et Betica Selma ont été identifiées au Burkina Faso. Indépendamment de la méthode utilisée, la prévalence du déficit enzymatique était significativement plus élevée chez les hommes (2, 5–20, 5%) comparativement aux femmes (3, 3–12, 3%). Conclusion Cette revue systématique suggère qu'en dépit de l'ubiquité du variant G-6-PD A- 202A/376G au Burkina Faso, il est. nécessaire de prendre en compte les variants Santamaria et Betica Selma, bien que leurs fréquences restent à préciser. Un dépistage systématique de la déficience en G-6-PD est. également nécessaire pour prévenir la survenue d'accidents hémolytiques iatrogènes notamment chez les populations les plus vulnérables au paludisme.